Respuesta :
Answer:
[tex]f^{-1}(x)=\frac{1}{4}x+3[/tex]
Step-by-step explanation:
We have been given the function [tex]f(x)=4x-12[/tex]
Below are steps for finding the inverse of the function.
Step 1:
Replace f(x) with y
[tex]y=4x-12[/tex]
Step 2:
Interchange x and y
[tex]x=4y-12[/tex]
Step 3:
Solve for y
[tex]x+12=4y\\\\y=\frac{1}{4}x+3[/tex]
Step 4:
Replace y with [tex]f^{-1}(x)[/tex]
[tex]f^{-1}(x)=\frac{1}{4}x+3[/tex]
Answer:
Then for the second question, it would be the third option
Step-by-step explanation:
on edg 2020